Harnessing Artificial Intelligence for the Reinforcement of Islamic Values: A Transformation in Madrasah Education - Irpani, Ayit (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study analyzes the transformation of Islamic education in madrasahs through the integration of Artificial Intelligence (AI) technology as a means to strengthen Islamic values. The research aims to understand how AI can be utilized not only to enhance learning effectiveness but also to support the internalization of moral and spiritual principles in education. Using a qualitative approach with a case study design, the research was conducted in two madrasahs that have adopted AI-based learning systems. Data were collected through in-depth interviews, participant observation, and documentation, and then analyzed using thematic analysis. The findings indicate that AI technology significantly enhances learning personalization, efficiency, and student engagement. Nonetheless, the success of this digital transformation relies on the teacher’s role as a moral and spiritual facilitator rather than a passive technology user. Teachers consciously embed Islamic values such as honesty (ṣidq), discipline (istiḳāmah), and responsibility (amānah) within AI-assisted learning interactions. However, several challenges remain, including limited digital infrastructure, insufficient teacher training in AI literacy, and the absence of formal policies supporting the systematic integration of Islamic values. This study concludes that the transformation of Islamic education in the AI era must harmonize technological innovation with spiritual and ethical guidance. The synergy between technology, educators, and institutional policy is crucial to developing adaptive, value-based Islamic education.